Genetic diversity of Falcataria moluccana and its relationship to the resistance of gall rust disease - NEO ENDRA LELANA; SURYO WIYONO; GIYANTO GIYANTO; ISKANDAR Z. SIREGAR (Society for Indonesian Biodiversity, 2018)
Lelana Ne, Wiyono S, Giyanto, Siregar IZ. 2018. Genetic diversity of Falcataria moluccana and its relationship to the resistance of gall rust disease. Biodiversitas 19: 12-17. The use of cultivars that are resistant to a particular disease is one strategy that could mitigate the incidence of gall rust disease on Falcataria moluccana. Previous studies on the genetic diversity of F. moluccana did not attempt to link that genetic diversity to gall rust disease resistance. This research was carried out using RAPD analysis to determine the preliminary information on the association between different markers and the resistance to gall rust disease. The analysis evaluated a total of 20 pairs of healthy and infected F. moluccana trees that were classified based on their disease severity level. The RAPD primers used in this study were as follows: OPA-05, OPA-08, OPA-10, OPA-13, OPA-18, OPB-07, OPD-13, OPF-02, and OPG-05. The results showed that each RAPD primer produced a varying number of polymorphic bands, ranging from 3 to 12 bands, with a total of 80 polymorphic bands. Despite the number of loci analyzed, however, no specific polymorphic bands were found that could distinguish between healthy and diseased trees. This was supported by principal component analysis, which showed that healthy and diseased populations were not distributed separately. The structure analysis also showed that the healthy and diseased populations were not different.